Student Vaccine Knowledge and Willingness to Receive Covid-19 Vaccines in School - Jihan Zia ‘Ufairah; Nurmalahayati Nurdin (TDMRC, Universitas Syiah Kuala, 2022)
Vaccination against COVID-19 has become mandatory for all educational institutions in Indonesia. The vaccine can help instructors, education staff, and students prevent the spread of COVID-19 in schools. However, awareness and willingness to get the covid-19 vaccine may be influenced by their knowledge of vaccines and several other factors. For instance, the spread of rumors about vaccines makes people fear the vaccine's side effects and make them reluctant to get the covid-19 vaccine. This study aims to analyze the relationship between knowledge and willingness to obtain COVID-19 vaccination in high school students. The research method employed involved an initial observation, 122 students receiving questionnaires, and seven students being interviewed. Using the Spearman Rho correlation test, the data analysis was evaluated to identify the level of knowledge of attitudes and attitudes toward vaccination doses. The outcomes of the interviews were then described, followed by data analysis. The result shows that 117 (94.9%) of the 122 participants in this study had a good level of awareness, and 40 (32.8%) had a favorable attitude toward their willingness to get the vaccine. The Spearman correlation test revealed a significant correlation between attitudes and knowledge (r = 0.296, p-value = 0.001) as well as a positive correlation between attitudes and vaccination doses (r = 0.183, p-value = 0.044). It shows there is a considerable correlation between these two relationships. Finally, the study concluded a significant correlation between knowledge and willingness to get covid-19 vaccination in students of Private Senior High School (MAS) Ulumul Quran Banda Aceh.